2021
DOI: 10.1016/j.jcct.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitral annular calcification in the elderly – Quantitative assessment

Abstract: To determine the reliability of subjective and objective quantification of mitral annular calcification (MAC) in elderly patients with severe aortic stenosis, to define quantitative sex-and age-related reference values of MAC, and to correlate quantitative MAC with mitral valve disease. Methods: In this retrospective, IRB-approved study, we included 559 patients (268 females, median age 81 years, inter-quartile range 77-85 years) with severe aortic stenosis undergoing CT. Four independent readers performed sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…In contrast, disjunctive annulus show a paradoxical systolic expansion and flattening, even in patients with preserved left ventricular function, indicating a functional decoupling from the ventricle [ 3 ]. Severe aortic stenosis and severe mitral regurgitation frequently coexists [ 18 , 19 ]. Whether mitral valve disease is independently associated with worse outcomes after TAVR remains a matter of debate [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, disjunctive annulus show a paradoxical systolic expansion and flattening, even in patients with preserved left ventricular function, indicating a functional decoupling from the ventricle [ 3 ]. Severe aortic stenosis and severe mitral regurgitation frequently coexists [ 18 , 19 ]. Whether mitral valve disease is independently associated with worse outcomes after TAVR remains a matter of debate [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CT allows for an assessment of the mitral valve apparatus including the leaflet/annulus complex with high accuracy [ [14] , [15] , [16] , [17] ]. In patients with aortic stenosis undergoing transcatheter aortic valve replacement (TAVR) relevant mitral valve disease frequently coexists in around one third of patients [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…5. Calculation of the mitral Agatston score 12,13,25 has been described as an alternative. Recently, researchers suggested that quantitative MAC scoring by the Agatston method is more reliable than visual assessment and has high accuracy to diagnose MS in elderly patients with aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…9 Multidetector computed tomography (MDCT) is now considered the gold standard for the detection of cardiac calcification. 2,[7][8][9][10][11][12][13] Although frequently applied to the aortic valve, [14][15][16][17] quantitative assessment of mitral calcium volume (MCV) has not been well studied and MAC as a disease has been poorly described. We assess the impact of MAC quantified by MCV on MV function and clinical outcomes after TAVI.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, contrast CT images enable the evaluation of other anatomical cardiac structures (coronary arteries and aorta), peri coronary fat attenuation index, cardiac volumes, ejection fraction, wall motion and intracardiac thrombus without additional imaging [32]. However, it is not possible to obtain the trans mitral gradients and associated MR with CT. [46]. The association between MAC and aging is proven by the fact that it is present in 90years of adults at the time of autopsy (17% men and 43% women) [47].…”
Section: Computed Tomographymentioning
confidence: 99%